International disorder and national identity. History and fable - La Torre, Massimo (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2019)
After World War Two a gigantic effort was made in order to build a viable and stable international order, beginning with the Bretton Woods agreement that was aimed to stabilize the international monetary system, and with the United Nations, that were intended to restore legality in interstate affairs and somehow initiate a cosmopolitan conversation among Nation States. This order is now slowly crumbling down, paradoxically through globalization, and a triumphant neoliberalism. A new, but indeed quite old narrative, rather a myth, of what a national identity means is again getting the upper hand.
Keywords: international relations; international law; European Union; globalization; national identity